What is the Libano-Québécois? Representing the Migrant Subject in Québec National Cinema - Ransom, Amy (Nouvelles vues)

(untitled) (Observatoire du cinéma au Québec, 2022)
This article analyzes how a body of twenty-first-century Québécois films featuring Lebanese (or Syrian) protagonists construct the migrant subject in relation to place and gender. It examines how its corpus—Wajdi Mouawad’s Littoral (2004), Ivan Grbovic’s Romeo Onze (2011), Samer Najari’s Arwad (2013) and three films by Maryanne Zéhil, De ma fenêtre sans maison (2006), La vallée des larmes (2012), and L’autre côté de novembre (2016)—portrays male or female protagonists experiencing identity crises as they negotiate the entre-deux, the in between, of migrant identities. These films represent what Homi K. Bhabha has called “third space interventions” by (mostly) migrant filmmakers and they seek to combat what has been identified as a “state-sponsored amnesia” about the Lebanese Civil.